2023
DOI: 10.1002/pros.24519
|View full text |Cite
|
Sign up to set email alerts
|

Adverse metabolic consequences of androgen deprivation therapy (ADT) on Asian patients with prostate cancer: Primary results from the real‐life experience of ADT in Asia (READT) study

Abstract: Background: Androgen deprivation therapy (ADT) use in prostate cancer (PCa) has seen a rising trend. We investigated the relationship between ADT and adverse changes in metabolic parameters in an Asian population.Methods: This is an international prospective multicenter single-arm cohort yielded from the real-life experience of ADT in Asia (READT) registry. Consecutive ADTnaïve patients diagnosed of PCa and started on ADT were prospectively recruited from 2016 and analyzed. Baseline patient characteristics, PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A total of 18 consensus statements (Table 1) were accepted and the rationale for each is described below. A number of studies of patients with PCa in Asia including Hong Kong have revealed that ADT users have higher risks of heart failure, hypertension, new-onset diabetes mellitus, dyslipidemia, and being overweight, compared with non-ADT users (11)(12)(13)(14)(15)(16)(17)(18). The association between ADT and an increased risk of developing cardiometabolic complications involves multiple factors, which include a decrease in the testosterone level, an elevation in follicle-stimulating hormone (FSH), changes in body composition, increased insulin resistance, and endothelial dysfunction (77).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 18 consensus statements (Table 1) were accepted and the rationale for each is described below. A number of studies of patients with PCa in Asia including Hong Kong have revealed that ADT users have higher risks of heart failure, hypertension, new-onset diabetes mellitus, dyslipidemia, and being overweight, compared with non-ADT users (11)(12)(13)(14)(15)(16)(17)(18). The association between ADT and an increased risk of developing cardiometabolic complications involves multiple factors, which include a decrease in the testosterone level, an elevation in follicle-stimulating hormone (FSH), changes in body composition, increased insulin resistance, and endothelial dysfunction (77).…”
Section: Resultsmentioning
confidence: 99%
“…Diagnostic criteria for the syndrome include 3/5 of the following criteria: fasting plasma glucose level > 110 mg/dL, serum triglyceride level ≥ 150 mg/dL, serum HDL < 40 mg/dL, waist circumference > 102 cm, and blood pressure ≥ 130/85 mmHg [ 11 ]. A study of Asian men with prostate cancer who received ADT showed significant changes in metabolic parameters during the treatment course [ 12 ]. A 4.8% increase in fasting blood glucose and 2.7% increase in HbA1c were both noted at 6 months as well as increased triglycerides and mean body weight during follow-up.…”
Section: Cardiovascular Risk Of Hormone Therapymentioning
confidence: 99%